Republic of North Macedonia : Central Bank Transparency Code Review. (IMF Staff Country Reports; Country Report ;, 2022)
The National Bank of the Republic of North Macedonia (NBRNM) is implementing advanced transparency practices. The long-standing commitment to transparency noted by a number of stakeholders and forcefully re-affirmed in the recent period is well anchored in the law, and it has been designated by the NBRNM as a strategic objective to fulfill its mandate. This policy has earned the NBRNM noteworthy trust from stakeholders met by the mission, and it has paid significant dividends in terms of anchoring its autonomy and ensuring policy effectiveness.